2006
DOI: 10.1089/pho.2006.24.655
|View full text |Cite
|
Sign up to set email alerts
|

Optical Absorption Coefficient, Time of Thermal Relaxation, Time of Surface Threshold, and Time of Heat Incubation for PMMA Samples at the CO2Laser-Beam Wavelength of 10.6 µm

Abstract: The value of alpha = 502 (cm(1)) for PMMAat 10.6 microm was identified, matching other results reported in the literature for similar compact media in the absence of water content, such as PMMA. The time of thermal relaxation was 9.358 x 10(4) sec, the time of surface threshold was 9.365 x 10(4) sec, and the time of heat incubation was 3.6 x 10(7) sec (all three for PMMAat 10.6 microm for any exposure). Using the calculated value of alpha, one of the practical clinical recommendations would be, for instance, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In the laser cutting process of a plate of homogeneous and isotropic material absorbing a monochromatic and parallel laser beam of incident power density I 0 , which gives the power density I at depth z, the value of I can be given as I = I 0 e µz where µ is the linear absorption coefficient (cm −1 ) [20] and its value for PMMA ranges from 10 2 to 10 5 cm −1 [19]. The absorption coefficient is independent of the polymer molecular weight [30] and for PMMA, it is 502 cm −1 at the wavelength of 10.6 µm [33]. Figure 1 shows a Gaussian-like profile cross-section of 96.7 kDa PMMA at a laser power and speed of 1 W and 7.04 mm s −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In the laser cutting process of a plate of homogeneous and isotropic material absorbing a monochromatic and parallel laser beam of incident power density I 0 , which gives the power density I at depth z, the value of I can be given as I = I 0 e µz where µ is the linear absorption coefficient (cm −1 ) [20] and its value for PMMA ranges from 10 2 to 10 5 cm −1 [19]. The absorption coefficient is independent of the polymer molecular weight [30] and for PMMA, it is 502 cm −1 at the wavelength of 10.6 µm [33]. Figure 1 shows a Gaussian-like profile cross-section of 96.7 kDa PMMA at a laser power and speed of 1 W and 7.04 mm s −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The thermal constants (specific heat capacity: c % 1,500 J kg À1 8C À1 [20]; thermal conductivity: K % 0.197 W m À1 8C À1 [20]; and convective heat transfer coefficient: h % 8 W m À2 8C À1 [21]) of Lucite are of the same order of magnitude of most tissues. Lucite also highly absorbs CO 2 laser radiation (m % 50,200 m À1 [22]) and barely absorbs the diode laser radiation (m % 0 m À1 , measured using an FTIR). Therefore, the two-wavelength system could be used to heat the upper and lower surfaces of such a phantom.…”
Section: Part 1: Simulations and Experiments On Lucite Plates That Sementioning
confidence: 99%
“…CO 2 laser cutting of PMMA with controlled parameters results in clean medical structures with minimal heat-affected zones. 10 Chen et al showed that CO 2 lasers are a simple and convenient processing method for micro-channel fabrication of various shapes on PMMA material by controlling the laser powers. 11 Kurt et al utilize ANOVA and regression methods to study the influence of process parameters on kerf-width and showed that workpiece thickness also affects the dimensional accuracy apart from other parameters.…”
Section: Introductionmentioning
confidence: 99%